The Interpretative Structural Modeling for Stakeholder Involvement to Reduce Slum Settlements - Bich, Bich Hanes; Rarasati, Ayomi Dita (Smart City, 2024)
The array of problems originating from slum settlements not only results in unwholesome environment, unlawful land utilization, and various internal challenges within the vicinity but also impacts the surrounding regions and the overall urban infrastructure network. In pursuit of Indonesia's 2045 Vision, which emphasizes on "equitable and integrated infrastructure development", the zero slums constitutes a pivotal component of the Ministry of Public Works and Public Housing's overarching vision. Nonetheless, a disparity has been identified in addressing slum settlements in West Kalimantan, hindering the achievement of this objective. This research aims to identify the stakeholders and the priority factors in determining the priority setting for slum area management in West Kalimantan. The method used in this research is semi-structured interview to identify and map stakeholders involved in priority setting, and geometric mean to identify influential factors which will then be analyzed using Interpretative Structural Modeling. The results found are that there are 24 stakeholders who are considered to be involved. Quadrant D (Manage Closely) stakeholders and primary stakeholders are members of the supervisory team, namely the Head of the Housing and Settlement Area Office, and the Head of the Regional Development Planning Agency. However, the highest level of influence is held by the steering committee while the highest level of interest is held by Housing and Settlement Area Office. In addition, ten categories with 22 factors are identified with nine ranking levels found to influence the decision to prioritize slum upgrading. The most influential factor is the difference in knowledge and experience between the new and the former team members.